Safety of the feed additive consisting of disodium 5′‐inosinate (IMP) produced by Corynebacterium stationis KCCM 80235 for all animal species (CJ Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety of disodium 5′‐inosinate (also known as inosine monophosphate, IMP) produced by Corynebacterium stationis KCCM 80235 as a sensory additive, functional group flavouring compounds, for all animal species. In 2022, the FEEDAP Panel issued an opinion on the safety and efficacy of the product. In that assessment, the Panel could not conclude on the safety of the additive for the target species, consumers, users and the environment due to uncertainties on the genetic basis of the streptomycin resistance of the production strain C. stationis KCCM 80235 and on the possible presence of its recombinant DNA in the final product. The applicant provided supplementary data which elucidated the genetic basis of the streptomycin resistance of the production strain and excluded the presence of its DNA in the final product. Therefore, the FEEDAP Panel concluded that IMP produced by C. stationis KCCM 80235 is safe for the target species, consumers, users and the environment. The FEEDAP Panel reiterated its previous concerns on the safety for the target species when using IMP in water for drinking due to hygienic reasons.